2015
DOI: 10.1002/ar.23172
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3k9 and H3k27 Acetylation Regulates IL‐4/STAT6‐Mediated Igε Transcription in B Lymphocytes

Abstract: IL-4 activates STAT6 and causes the subsequent up-regulation of Ig heavy chain germline Ige via chromatin remodeling involved in B lymphocytes development. STAT6 acts as a molecular switch to regulate the higher-order chromatin remodeling via dynamically orchestrating co-activators (CBP/Tudor-SN) and co-repressors (HDAC1/PSF). Here, we demonstrated that STAT6/Tudor-SN/PSF form a complex, balancing the acetylation and deacetylation states to co-regulate IL-4/STAT6 gene transcription. In addition, we confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Previous evidence suggests that ACLY phosphorylation and activity regulate gene expression via histone acetylation in macrophages [17] and osteoclasts [38]. Moreover, IL4-driven histone acetylation is an important regulator of gene expression in B-lymphocytes [23] and macrophages [39,40], and the histone acetyltransferase P300/CBP is well recognized as an important mediator of IL4-stimulated gene regulation [41,42]. In our hands, IL4 treatment induced relatively small increases in total histone acetylation.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Previous evidence suggests that ACLY phosphorylation and activity regulate gene expression via histone acetylation in macrophages [17] and osteoclasts [38]. Moreover, IL4-driven histone acetylation is an important regulator of gene expression in B-lymphocytes [23] and macrophages [39,40], and the histone acetyltransferase P300/CBP is well recognized as an important mediator of IL4-stimulated gene regulation [41,42]. In our hands, IL4 treatment induced relatively small increases in total histone acetylation.…”
Section: Discussionsupporting
confidence: 55%
“…Our results indicated that lysates from IL4-treated cells were enriched in acetyl-lysine-positive histone H3 (Figure 4B). We then investigated specific acetylation marks that have been associated with IL4-mediated gene regulation [23]. Histones that were isolated from IL4-stimulated cell lines showed small increases in global acetylation of H3K9 and H3K27 acetylation compared with controls (Figure 4C).…”
Section: Histone Acetylation Leading To Gene Expression Changes Is Al...mentioning
confidence: 99%
“…A possible mechanism to bridge this temporal gap is epigenetics, stable and long-lasting gene expression variations induced by non-DNA-encoded mechanisms such as DNA methylation, histone modification, and RNA modification 107,108 . It has been reported that STAT6 modulates both permissive and repressive histone modifications like H3K27ac, H3K9ac, and H3K27me3 101,109 . Considering that numerous studies have suggested a relationship between these histone modifications and the pathophysiology of depression 110,111 , further investigation of these histone modifications in the DRN serotonin neurons in a cell-type selective manner will provide insights into the complete picture of how antidepressants induce chronic transcriptomic changes through transient activation of IL-4-STAT6 signaling by using chromatin profiling methods applicable for a small number of cells such as CUT&Tag 112 .…”
Section: Discussionmentioning
confidence: 99%
“…Tudor-SN also acts as a transcriptional coactivator of PPARc, a key transcription factor in adipocyte differentiation, and assists PPARc in promoting adipocyte differentiation and lipid droplet formation by enhancing histone acetylation [25]. In addition to binding to transcription factors, Tudor-SN can affect chromatin conformation and regulate gene transcription by recruiting the histone acetyltransferases GCN5 and CBP/p300 or the ATP-dependent chromatin remodeler SMARCA5 [16,25,[27][28][29][30][31].…”
Section: Dna Transcriptionmentioning
confidence: 99%